Heart regeneration for clinical application update 2016: from induced pluripotent stem cells to direct cardiac reprogramming - Yamakawa, Hiroyuki (Inflamm Regen, 2016)
Cardiovascular disease remains a major cause of death for which current therapeutic regimens are limited. Following myocardial injury, endogenous cardiac fibroblasts, which account for more than half of the cells in the heart, proliferate and synthesize extracellular matrix, leading to fibrosis and heart failure. As terminally differentiated cardiomyocytes have little regenerative capacity following injury, the development of cardiac regenerative therapy is highly desired. Embryonic stem and induced pluripotent stem (iPS) cells are promising tools for regenerative medicine. However, these stem cells demonstrate variable cardiac differentiation efficiency and tumorigenicity, which must be resolved prior to clinical regenerative applications. Until the last decade, an established theory was that cardiomyocytes could only be produced from fibroblasts through iPS cell generation. In 2010, we first reported cardiac differentiation from fibroblasts by direct reprogramming, and we demonstrated that various cardiac reprogramming pathways exist. This review summarizes the latest trends in stem cell and regenerative research regarding iPS cells, a partial reprogramming strategy, and direct cardiac reprogramming. We also examine the many recent advances in direct cardiac reprogramming and explore the suitable utilization of these methods for regenerative medicine in the cardiovascular field.